2013
DOI: 10.1515/sg-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Provenance variation in height development of Albizia falcataria under three levels of spacing in East Java, Indonesia

Abstract: Nine provenances of Albizia falcataria were planted at three square spacing levels (2, 3, and 4 m) in a split-plot design at Jember in East Java, Indonesia and measured annually for six years, which is three quarters of its rotation age. The effect of spacing on mean height development became progressively evident, due to the decline in growth at closer spacing caused by intensified competition, in six provenances, i.e., three provenances each from Java and East Indonesia, which were considered better adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The result for WD is inconsistent of Kojima et al (2009b), who reported negative or no changes of WD out along the DBH in Indonesian plantation. This difference might be related to differences in ages (23-yearold in our study vs. 7 to 8-year-old in Kojima et al 2009b), planting density, and genetic origins within Indonesia (Kurinobu et al 2013). We also found that F. falcata produced light wood earlier, and dense wood later.…”
Section: Discussionmentioning
confidence: 61%
“…The result for WD is inconsistent of Kojima et al (2009b), who reported negative or no changes of WD out along the DBH in Indonesian plantation. This difference might be related to differences in ages (23-yearold in our study vs. 7 to 8-year-old in Kojima et al 2009b), planting density, and genetic origins within Indonesia (Kurinobu et al 2013). We also found that F. falcata produced light wood earlier, and dense wood later.…”
Section: Discussionmentioning
confidence: 61%